Entre serras e sertões A(s) (trans)formaç(ões) de centralidade(s) da Região Metropolitana do Cariri/CE - Gurgel, Ana Paula Campos (2012)
This study reviews the spatial configuration from the road network of an urban compound formed by the cities of Crato, Juazeiro do Norte and Barbalha (the Crajubar - core of the Cariri metropolitan region, in the State of Ceará, Brazil), in order to establish nexus (or relations) between different levels of accessibility and the formation/ transformation and specialization of centralities in local and metropolitan scales. Stemming from the Social Logic of Space theoretical and operational apparatus, the study explores modeling possibilities (with axial lines, segments and lines of continuity) which is then confronted to empirical observations concerning movement flows and land use, within a Geographic Information System database. At different scales of analysis, the results suggest evidences of continuity were found in the permanence of intra-urban centres and sub-centres within each town, whereas evidences of change pointed out to the formation of a new centrality of metropolitan magnitude in the neighbourhood referred to as the Triângulo, in the municipality of Juazeiro, where high levels of topological accessibility coincides with the appearance of new business buildings as well as with the emergence of urban equipment of a scale more adequate to meet a regional demand